Moving ahead in science and technology 10 - Ramirez, Rachel Patricia B.; Regalado,-Taduran, Regina Carla; Pineda, Laurice; Bojo, Zenaida (Quezon City : FNB Educational, Inc., 2018)
FNB presents to you Moving Ahead in Science and Technology 10, the fourth book in an innovative series for junior high school students. The book is equip you with the perfect balance of content and activities in science and technology, which are thoroughly discussed, explored, and integrated and applied.
Includes bibliography
English text.
Keywords: Physical science